Acute kidney injury in COVID-19 pediatric patients in North America: Analysis of the virtual pediatric systems data - Raina, Rupesh; Mawby, Isabelle; Chakraborty, Ronith; Sethi, Sidharth Kumar; Mathur, Kashin; Mahesh, Shefali; Forbes, Michael (PLOS ONE, 2022)
Background Despite extensive research into acute kidney injury (AKI) in adults, research into the epidemiology, associated risk factors, treatment, and mortality of AKI in pediatric COVID-19 patients is understudied. Advancing understanding of this disease is crucial to further developing treatment and preventative care strategies to reduce morbidity and mortality. Methods This is a retrospective analysis of 2,546 COVID-19 pediatric patients (age ≤ 21 years) who were admitted the ICU in North America. Analysis of the Virtual Pediatric Systems (VPS) COVID-19 database was conducted between January 1, 2020, and June 30, 2021. Results Out of a total of 2,546 COVID positive pediatric patients, 10.8% (n = 274) were diagnosed with AKI. Significantly higher continuous and categorical outcomes in the AKI subset compared to the non-AKI cohort included: length of stay at the hospital (LOS) [9.04 (5.11–16.66) vs. 5.09 (2.58–9.94) days], Pediatric Index of Mortality (PIM) 2 probability of death [1.20 (0.86–3.83) vs. 0.96 (0.79–1.72)], PIM 3 probability of death [0.98 (0.72–2.93) vs. 0.78 (0.69–1.26)], mortality [crude OR (95% CI): 5.01 (2.89–8.70)], airway and respiratory support [1.63 (1.27–2.10)], cardio-respiratory support [3.57 (1.55–8.23)], kidney support [12.52 (5.30–29.58)], and vascular access [4.84 (3.70–6.32)]. Conclusions This is one of the first large scale studies to analyze AKI among pediatric COVID-19 patients admitted to the ICU in North America. Although the course of the COVID-19 virus appears milder in the pediatric population, renal complications may result, increasing the risk of disease complication and mortality.